1997
DOI: 10.2190/ljuq-19h1-ulkc-dt1h
|View full text |Cite
|
Sign up to set email alerts
|

Culture as a Decision Variable for Designing Computer Software

Abstract: Computer software design generally follows a systematic process that addresses decisions on variables known to influence learning success. We propose that culture should be included as part of this decision process. Culture represents the complex of social, emotional, intellectual, physical, and personal factors that individuals use to create meaning. When these cognitive anchors are missing from instructional materials, achievement may be imperiled. Examples of how cultural variables can be incorporated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Cultural uniqueness is manifest on many different social levels, and these different levels are often referred to as communities. A community can be broadly defined as a nation, social class, or race, or it can be more specifically defined as an organization or club, a neighborhood, a church, mosque, or temple, or a school (Williams-Green, Holmes, & Sherman, 1997 ). Along similar lines, Lauzon ( 1999 ) refers to communities of practice.…”
Section: Culture and Learningmentioning
confidence: 99%
“…Cultural uniqueness is manifest on many different social levels, and these different levels are often referred to as communities. A community can be broadly defined as a nation, social class, or race, or it can be more specifically defined as an organization or club, a neighborhood, a church, mosque, or temple, or a school (Williams-Green, Holmes, & Sherman, 1997 ). Along similar lines, Lauzon ( 1999 ) refers to communities of practice.…”
Section: Culture and Learningmentioning
confidence: 99%
“…2002), which influences people's behaviour, perspectives, values, and understanding. It is widely accepted that culture shapes individuals' perceptions of innovations that bear directly on their lives (Williams‐Green et al . 1997; Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addressing the postcolonial administration of education in rural Alaska, Deniro (2004) found that although the curriculum was "well meaning," it was "often culturally insensitive" (p. 401) and was implemented with little regard for indigenous values. It has been widely documented that culture plays an important role in how innovations such as the use of computer technologies are adopted (Albirini, 2006;Williams-Green, Holmes, and Sherman, 1997;Straub, Keil, and Brenner, 1997). Haynes Writer (Wimburg and others, 2003) provides an insightful response to how indigenous people such as Alaska Natives are "operating within an economic and cultural schism" with regard to technology and suggests that native people "must be creative in our use of technology so we are in control of it rather than having it control us" (p. 34).…”
Section: The Culture Factormentioning
confidence: 99%